Crystal structure and Hirshfeld surface analyses, interaction energy calculations and energy frameworks of methyl 2-[(4-cyanophenyl)methoxy]quinoline-4-carboxylate - Ayoub El-Mrabet; Amal Haoudi; Frederic Capet; Tuncer Hökelek; Mazzah Ahmed (Acta Crystallographica Section E: Crystallographic Communications)
The title compound, C19H14N2O3, features competition and interplay of a range of weak interactions, which actualize under the absence of conventional hydrogen-bond donors. Two kinds of stacking interactions, namely slipped antiparallel interactions of cyanophenyl groups as well as quinoline and carboxy groups, are primarily important. In combination with relatively short tetrel OCH3...N[triple-bond]C bonds [C...N = 3.146 (3) Å] they are responsible for the generation of the layers, while the interlayer bonding occurs via C—H...O and C—H...N weak hydrogen bonds. These findings are consistent with the results of Hirshfeld surface analysis and calculated interaction energies. Contributions of the C...C, C...N/N...C and C...O/O...C contacts originating in the stacking interactions account for 17.0% to the surface area. The largest interactions energies are associated with the two kinds of stacks (−45.8 and −24.3 kJ mol−1) and they are superior to the energies of weak hydrogen bond and tetrel interactions (−12.4 to −22.4 kJ mol−1). Evaluation of the electrostatic, dispersion and total energy frameworks indicate that the consolidation is dominated via the dispersion energy contributions.